Nondestructive On-Site Detection of Soybean Contents Based on An Electrothermal MEMS Fourier Transform Spectrometer - Donglin Wang (IEEE Photonics Journal, 2019)
A portable spectrophotometer has been developed to provide on-site detection of soybeans' moisture, protein, and fat contents in a nondestructive manner. The core module of this soybean analyzer is a micro Fourier transform infrared spectrometer (μFTIR) based on an electrothermal microelectromechanical systems (MEMSs) mirror. The electrothermal MEMS mirror is capable of generating a large piston motion of 320 μm at only 8.5 Vdc. The tilting of the MEMS mirror plate during its piston scanning affects the spectral repeatability of the μFTIR. In this paper, the effect of the MEMS mirror tilting on the spectral repeatability is analyzed and an automatic tilt realignment algorithm is developed to maintain high spectral repeatability, which is better than 0.01 in long term use. The μFTIR module has a footprint of 125 mm × 90 mm with a height of 50 mm. The whole instrument is designed for portability and on-site operation as well as the convenience of loading soybeans. More than 300 samples of soybeans are collected, 80% of which are used to establish a prediction model using chemometrics methods. The standard error is no more than 3% when using the prediction model to test the remaining 20% samples.